2019
DOI: 10.21079/11681/34072
|View full text |Cite
|
Sign up to set email alerts
|

Forest Cover Index for tree cover detection using Landsat-7 multispectral imagery

Abstract: Forest cover monitoring using satellite imagery is important to U.S. military terrain analysis. Mobility models, cover and concealment, and precise surface feature delineation all rely on an accurate forest/nonforest cover layer. However, the challenge remains in distinguishing trees from other vegetative land covers when relying on single date imagery. A Forest Cover Index (FCI) algorithm was previously developed on Worldview-2 imagery and was designed to separate forest cover from nonforest covered areas. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…While there was no consistent difference in seasonal accuracy, perhaps due to the disparate nature of the biome conditions, seasonal changes such as flooding, snow, and tree senescence did reduce the accuracy of the FCI in specific images. This aligns with previous research by Becker et al (2018) and Feliciano-Cruz et al (2019) who found clear delineation with the FCI between tree cover and the other land covers in the image, including agriculture and built-up land, Becker et al (2018) also found a seasonal component.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…While there was no consistent difference in seasonal accuracy, perhaps due to the disparate nature of the biome conditions, seasonal changes such as flooding, snow, and tree senescence did reduce the accuracy of the FCI in specific images. This aligns with previous research by Becker et al (2018) and Feliciano-Cruz et al (2019) who found clear delineation with the FCI between tree cover and the other land covers in the image, including agriculture and built-up land, Becker et al (2018) also found a seasonal component.…”
Section: Discussionsupporting
confidence: 92%
“…Accuracies were lower in comparison to Becker et al (2018); however, Becker et al (2018) only examined one study site and used a less robust non-random sampling accuracy assessment technique, which could have inflated their accuracy. The Kappa values of this research were consistent with the Kappa value that Feliciano-Cruz et al (2019) derived from an error analysis using random sampling.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations